Body size preferences and food choice among mothers and children in Malawi - Valerie L. Flax; Chrissie Thakwalakwa; John C. Phuka; Lindsay M. Jaacks (Wiley, 2020)
Abstract Overweight in mothers and children in sub‐Saharan Africa is rapidly increasing and may be related to body size perceptions and preferences. We enrolled 268 mother-child (6-59 months) pairs in central Malawi; 71% of mothers and 56% of children were overweight/obese, and the remainder were normal weight. Interviewers used seven body silhouette drawings and a questionnaire with open‐ and closed‐ended questions to measure mothers' perceptions of current, preferred and healthy maternal and child body sizes and their relation to food choices. Overweight/obese and normal weight mothers' correct identification of their current weight status (72% vs. 64%), preference for overweight/obese body size (68% both) and selection of an overweight/obese silhouette as healthy (94% vs. 96%) did not differ by weight status. Fewer overweight/obese than normal weight mothers' preferred body silhouette was larger than their current silhouette (74% vs. 29%, p < .001). More mothers of overweight than normal weight children correctly identified the child's current weight status (55% vs. 42%, p < .05) and preferred an overweight/obese body size for the child (70% vs. 58%, p < .01), and both groups selected overweight/obese silhouettes as healthy for children. More than half of mothers in both groups wanted their child to be larger than the current size. Mothers said that increasing consumption of fruits, vegetables, meat, milk, grains, fizzy drinks and fatty foods could facilitate weight gain, but many cannot afford to purchase some of these foods. Their desired strategies for increasing weight indicate that body size preferences may drive food choice but could be limited by affordability.